2013
DOI: 10.1155/2013/972093
|View full text |Cite
|
Sign up to set email alerts
|

Healing of an Extensive Periradicular Lesion Subsequent to a Proper Endodontic Treatment of a Mandibular First Premolar with Complex Anatomy

Abstract: Long-term success of endodontic treatment is strictly dependent on proper shaping and cleaning of the root canal system followed by obturation of entire prepared space. Anatomical variations should be considered during radiographic and clinical evaluation as parts of endodontic treatment. A mandibular premolar with three canals is quite rare and such a tooth requires special canal preparation and obturation techniques. An astute clinician should identify different canal configurations and treat them endodontic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…14,15 However, most of the prior studies have either completely or partially destroyed the tooth during examination or have gained only two-dimensional anatomic information. Moreover, few studies have incorporated information such as ethnic background and sex of the study population, 12,3 which may have critical clinical ramifications for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 However, most of the prior studies have either completely or partially destroyed the tooth during examination or have gained only two-dimensional anatomic information. Moreover, few studies have incorporated information such as ethnic background and sex of the study population, 12,3 which may have critical clinical ramifications for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Root morphology and properties of human tooth tissues vary among different ethnic Populaces. 2,3 Since the endodontic treatment relies on upon the quality of clinical procedure, knowledge on root canal morphology is instrumental for the accomplishment of the treatment. 3,4 Quantities of studies have been directed for as far back as a…”
mentioning
confidence: 99%
“…Intracanal placement of calcium hydroxide has been proposed in necrotic cases because of its antimicrobial properties. It has been reported that treatment with calcium hydroxide results in high frequency of periapical healing and some lesions, especially those of younger patients, are significantly reduced or had completely disappeared in only 1-3 months after the treatment (32,33). Calcium hydroxide is proven to assist periapical healing by its antibacterial properties and also by its biological action facilitating osseous repair (34).…”
Section: Methods Using Calcium Hydroxidementioning
confidence: 99%